Decreased plasma APOA1 levels are associated with increased severity of placenta accreta spectrum disorders: a nested case-control study - Zeng, Shuai; Qu, Jiangxue; Jiang, Hai; Shi, Huifeng; Yan, Jie; Zhao, Yangyu; Chen, Lian (Frontiers in Endocrinology, 2025)
ObjectivePlacenta accreta spectrum (PAS) disorders are a series of gestational diseases, with severe adverse outcomes. Apolipoprotein A1 (APOA1) is a lipid molecule that plays a role in cell invasion, inflammation and immune response. This study aimed to elucidate the relationship between APOA1 and PAS, as well as its adverse outcomes.MethodsThis is a nested case-control study involving 118 patients with PAS and 118 non-PAS control women. Plasma APOA1 levels were evaluated at gestational weeks 24+0 to 35+6 by enzyme-linked immunosorbent assay. The clinical characteristics and pregnancy outcomes were recorded and analyzed in relation to APOA1 levels.ResultsThe plasma APOA1 level in the PAS group was observed to be lower than that in the non-PAS group (p = 0.035). From 24+0 to 35+6 weeks of gestation, the trajectory of plasma APOA1 levels in the placenta percreta (PP) and placenta increta group exhibited a discernible decline. Maternal plasma APOA1 is a significant biomarker for the diagnosis of PAS and its adverse outcomes, particularly in the 32+0 to 35+6 weeks of gestation range for invasive PAS (AUC = 0.761, 95% CI 0.660-0.863, p < 0.001), PP (AUC = 0.889, 95% CI 0.801-0.976, p < 0.001), blood transfusion (AUC = 0.729, 95% CI 0.620-0.838, p < 0.001) and hysterectomy (AUC = 0.884, 95% CI 0.790-0.978, p < 0.001).ConclusionsA reduction in maternal plasma APOA1 levels was associated with the severity of PAS. APOA1 may serve as a biomarker for invasive PAS, blood transfusion and hysterectomy in late gestation.